2021
DOI: 10.3390/ijerph182212197
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Telepractice Use during the COVID-19 Pandemic: Perspectives of Pediatric Speech-Language Pathologists

Abstract: The study investigated how pediatric speech-language pathologists (SLPs) applied telepractice to compensate for the loss of in-person services and the dynamics of telepractice use during the COVID-19 pandemic in a rural state. We conducted interviews with 10 SLPs and then a statewide survey in which 51 SLPs participated. The qualitative interviews revealed themes including changes in service environment due to the pandemic (e.g., transition to telepractice, losing clients), challenges in the transition to tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
3
23
3
1
Order By: Relevance
“…The high level of interest surrounding telehealth among non-user SLPs was also reported in a study conducted by ASHA [ 13 ], wherein 47% of SLPs in the latter study who never use telehealth showed an interest in using it in the future. For SLPs who used telehealth during the pandemic, a study found that around half of the respondents showed interest in using telehealth in the future regardless of the pandemic [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The high level of interest surrounding telehealth among non-user SLPs was also reported in a study conducted by ASHA [ 13 ], wherein 47% of SLPs in the latter study who never use telehealth showed an interest in using it in the future. For SLPs who used telehealth during the pandemic, a study found that around half of the respondents showed interest in using telehealth in the future regardless of the pandemic [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of these benefits broadly supports the findings of other studies in this area. In terms of convenience and accessibility, telehealth can allow SLPs to offer their services to and expand in rural communities in order to provide services to those patients [ 21 ] [ 28 , 30 ]. The last point is particularly important as most speech therapy services in Saudi Arabia are clustered in the largest cities; thus, patients need to travel long distances to reach services [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because telehealth has been used as a substitute for in-person services extensively, it is important to examine how people’s experiences with telehealth may affect their views toward its future use. Previous research based on clinicians showed that clinicians had a high regard toward telehealth during the pandemic, but only a small proportion of them anticipated continuous telehealth use when the pandemic is over [ 27 ]. However, little is known about the clients’ perspectives.…”
Section: Introductionmentioning
confidence: 99%